Leadership in a Major Science-Engineering Library Social and Political Factors and the Need to Communicate - Frank, Donald G. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1988)
This examination of the concept of leadership in the context of a large science-engineering library focuses on the importance of communication as it explores relevant social and political factors from an administrative perspective. The paper begins with an overview of the services and collections of the science-engineering library. The nature of leadership, including the importance of vision and communication, is then considered. A discussion of the environment of the science-engineering library--academic departments, students, other library administrators, and professional associations--follows. Categories of leadership roles of the administrator of the major science-engineering library are outlined: interpersonal roles (figurehead, leader, and liaison); informational roles (monitor, disseminator, and spokesman); and decisional roles (entrepreneur, disturbance handler, resource allocator, and negotiator). It is concluded that, although the major science-engineering library is unique, it is a microcosm of the main library, and the basic administrative skills needed to administer primary activities and operations are similar for the directors of both libraries. (4 references) (MES)
ERIC Note: Paper presented at the Library Administration and Management Association President's Program at the Annual Convention of the American Library Association (New Orleans, LA, July 10, 1988).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Academic Libraries; Administrator Role; Communication Skills; Communication (Thought Transfer); Higher Education; Leadership Styles; Library Administration; Library Associations; Users (Information); Science Libraries; Opinion Papers; Speeches/Meeting Papers